KERJASAMA ORANGTUA DAN GURU DALAM MENCEGAH PERILAKU BULLYING DI TK AL ADABIY KOTA PONTIANAK - Iftiza, Fachria; Syukri, M.; Amalia, Annisa (Universitas Tanjungpura, 2022)
This study aims to determine the cooperation of parents and teachers in the form of parenting, communicating, and learning at home for preventing early childhood bullying behavior at the Al Adabiy Kindergarten in Pontianak City. This study uses a descriptive quantitative method with the technique of distributing close ended questions to 105 parents of students and interviews with teachers. The analytical technique used is descriptive analysis, that is data analysis in research conducted by describing the data that has been collected through the presentation of statistical data. The results of the general calculation that all parents and teachers for preventing early childhood bullying behavior have a very good success rate category with a percentage calculation 77.85%. Cooperation in the form of parenting between parents and teachers for preventing early childhood bullying behavior with a calculation of percent to 74.05% which is classified as a success rate in the good category. Cooperation in the form of communicating between parents and teachers for preventing early childhood bullying behavior with a calculation of 79.89% percent belonging to the category of very good success rate, while cooperation in the form of learning at home between parents and teachers for preventing early childhood bullying with a percentage calculation to 78.20% which is classified as a very good success rate category.